2017
DOI: 10.1038/s41598-017-11518-0
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-22 level is negatively correlated with neutrophil recruitment in the lungs in a Pseudomonas aeruginosa pneumonia model

Abstract: Pseudomonas aeruginosa is a major threat for immune-compromised patients. Bacterial pneumonia can induce uncontrolled and massive neutrophil recruitment ultimately leading to acute respiratory distress syndrome and epithelium damage. Interleukin-22 plays a central role in the protection of the epithelium. In this study, we aimed to evaluate the role of interleukin-22 and its soluble receptor IL-22BP in an acute Pseudomonas aeruginosa pneumonia model in mice. In this model, we noted a transient increase of IL-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 44 publications
5
34
0
1
Order By: Relevance
“…98 However, this dose is 1000-fold >0.1 mg kg À1 used to induce a protective effect in the high-fat diet murine model. 88 It also contrasts with a murine model study of IL-22's role in Pseudomonas aeruginosa lung damage, 100 where neutralisation of IL-22 resulted in increased neutrophil infiltration, and lung damage. 100 The protection in this study followed treatment with 0.1 mg kg À1 of rIL-22 via intratracheal administration 18 hours prior to induction of acute pneumonia with the bacterium.…”
Section: Il-22 Dose Effectsmentioning
confidence: 97%
See 3 more Smart Citations
“…98 However, this dose is 1000-fold >0.1 mg kg À1 used to induce a protective effect in the high-fat diet murine model. 88 It also contrasts with a murine model study of IL-22's role in Pseudomonas aeruginosa lung damage, 100 where neutralisation of IL-22 resulted in increased neutrophil infiltration, and lung damage. 100 The protection in this study followed treatment with 0.1 mg kg À1 of rIL-22 via intratracheal administration 18 hours prior to induction of acute pneumonia with the bacterium.…”
Section: Il-22 Dose Effectsmentioning
confidence: 97%
“…88 It also contrasts with a murine model study of IL-22's role in Pseudomonas aeruginosa lung damage, 100 where neutralisation of IL-22 resulted in increased neutrophil infiltration, and lung damage. 100 The protection in this study followed treatment with 0.1 mg kg À1 of rIL-22 via intratracheal administration 18 hours prior to induction of acute pneumonia with the bacterium. 100 Similarly, a study of rIL-22 treatment in an airway disease model triggered by inhalation of methacholine 78 reported that IL-22 was protective at the more physiological dose of 0.1-10 mg kg À1 .…”
Section: Il-22 Dose Effectsmentioning
confidence: 97%
See 2 more Smart Citations
“…15 Neutralizing IL-22BP in the lung significantly increases survival and decreases neutrophilia in a mouse model of Pseudomonas aeruginosa. 16 Under naive conditions in the lung, alveolar epithelial cells and alveolar macrophages (AMs) have been identified as sources of IL-22BP, 17,18 and neutrophils are a source during catastrophic lung injury. 18 In the current study, we demonstrate that shifting the balance of the IL-22/IL-22BP axis in favor of IL-22 promotes recovery during influenza infection by promoting tight junction formation.…”
Section: Introductionmentioning
confidence: 99%